Minimnya Dukungan Industri dan Negara: Kerja Perawatan pada Perempuan Pekerja Pabrik dan Rumahan - Saleh, M Didit; Swastika, Nitya; Fatikhah, Rizki Amalia (Yayasan Jurnal Perempuan, 2023)
This article aims to delineate the systemic challenges and discrimination faced by women workers in the footwear and home-based industries, both in terms of working conditions and caregiving responsibilities. The findings of this study were obtained through in-depth interviews with women workers in three footwear factories in Banten Province and home-based workers in North Jakarta. The experiences of these women workers were analyzed within two interrelated domains: the realm of production and social reproduction. The research reveals that women workers, both in factories and home-based settings, face a dual burden, striving to meet high production targets while also bearing the responsibilities of caregiving. Specifically, women home-based workers are more vulnerable to health risks compared to factory workers due to the lack of separation between their workplace and living spaces. The study also uncovers that women workers in both factory and home-based settings encounter economic violence, as their caregiving work goes unpaid and lacks support from the government and the industry.